Management of the Implementation of the Kurikulum Merdeka at the Center of Excellence Vocational High School - Satriyanto, Kendrat; Niron, Maria Dominika (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The implementation of the Kurikulum Merdeka at Center of Excellence Vocational High Schools (PK) faces challenges, including limited industrial partners, inadequate practical facilities, insufficient teacher understanding, and limited access to technology. This study aims to analyze the management of implementing the Kurikulum Merdeka at the Center of Excellence Vocational High Schools (SMK PK). A descriptive qualitative method was used, with principals, vice principals, and teachers at three PK SMKs (SMK Negeri 1, 2, and 3 Tarakan) as subjects. Data were collected through in-depth interviews and documentation, and then analyzed using the interactive model developed by Miles, Huberman, and Saldana. The results indicate that curriculum planning is conducted through the development of the Educational Unit Operational Curriculum (KOSP), involving internal stakeholders. Implementation includes intracurricular learning, the Pancasila Student Profile-based P5 project, and internships, although hampered by the lack of industrial partners. Learning evaluation remains hindered by assessment instruments that are not aligned with the principles of the Kurikulum Merdeka. The study's conclusions underscore the importance of collaboration with the Business and Industry World (DUDI), increasing teacher capacity through training, and providing supporting facilities. The research implications recommend strengthening synergy between schools, the government, and DUDI to increase the relevance of the curriculum to the needs of the world of work and optimize project-based learning.